Writing the Body, Writing for the Body: Does the Tattoo Emerge as an Emblem of Defiance or a Manifestation of Reluctance? - Zoulagh, Latifa (Alternative francophone)

(untitled) (University of Alberta, Department of Modern Languages and Cultural Studies, 2026)
This article delves into the intricate landscape of Moroccan society, a traditional Arab-Muslim milieu often perceived as a realm where women are confined. Yet, within this cloistered existence, the emergence of the female voice manifests a rich tapestry of women’s writing. This literary production is deeply woven into collective feminine traditions, such as the enduring practices of tattooing and henna calligraphy, which serve as the foundation for a contemporary artistic and literary expression. By illuminating the female body as a canvas of liberation, these archaic forms of writing emerge as vital markers in the reclamation of feminine identity, reflecting the resolute spirit of Moroccan women in their quest for empowerment.